KELAYAKAN ENSIKLOPEDIA MATERI KEANEKARAGAMAN HAYATI DARI BUAH KALANTIK, ALUPM DAN TAROYOTN DI KABUPATEN BENGKAYANG - Betsi, Maria Regina; Daningsih, Entin; Titin, Titin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aimed to determine the feasibility of encyclopedia media for biodiversity material of class x high school from the morphology and nutrient content as well the fruit fiber of kalantik (Baccaureamacrocarpa (Miq.) M?ll.Arg), alupm (Aglaiasimplicifolia(Bedd.) Hams) and taroyotn (Horsfieldiacostulata (Warb.) in Tembawang Bagak, Bengkayang District The research was descriptive with purposive sampling technique. The making of encyclopedia media was followed by instrument validation and media validation. The instrument validation was in the form of instrument assessment sheet by two lecturers of Biology Education FKIP Tanjungpura University covering two aspects. Media validationwas done by five validators namely two lecturers of Biology Education FKIP Tanjungpura University, two biology teachers of class X high school in Bengkayang and one biology teacher in class X high school in Kubu Raya District covering four aspects with 13 criteria. The result of instrument validation showed that instrument items were feasible to use but corrected. Media validation the end of the Content Valdity Ratio (CVR) score and Content Validity Index (CVI) meet the minimum Lawshe limit value of 0.99 valid categories, so the encyclopedia was feasible to use as a learning media in schools.Keyword: Encyclopedia, Biodiversity, Kalantik, Alupm and Taroyotn